2012
DOI: 10.3109/02713683.2011.635402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cystoid Macular Edema Using Optical Coherence Tomography and Fundus Fluorescein Angiography after Uncomplicated Phacoemulsification Surgery

Abstract: Macular thickness changes after uncomplicated phacoemulsification surgery and Spectral domain OCT is helpful in detecting cystoid abnormalities and any increase in macular thickness at postoperative early periods. Changes seen on OCT do not completely correlate with FFA findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 23 publications
1
36
1
1
Order By: Relevance
“…9,14 However, in our study macular thickness increase was at subclinical level with no correlation between macular thickness changes and visual acuity. Interestingly, none of the preoperative and intraoperative parameters evaluated in this study, namely axial length, anterior chamber depth, status of vitreoretinal adhesion, length of surgery, effective phaco time and phaco energy, showed any correlation with retinal thickness changes after surgery.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…9,14 However, in our study macular thickness increase was at subclinical level with no correlation between macular thickness changes and visual acuity. Interestingly, none of the preoperative and intraoperative parameters evaluated in this study, namely axial length, anterior chamber depth, status of vitreoretinal adhesion, length of surgery, effective phaco time and phaco energy, showed any correlation with retinal thickness changes after surgery.…”
Section: Discussioncontrasting
confidence: 43%
“…In previous studies, subclinical macular thickening has been reported after uncomplicated cataract surgery. [9][10][11][12][13][14] Interestingly, in our study, at day 1 after surgery, mean retinal thickness of all macular subfields of the operated eyes decreased significantly in comparison to the fellow eyes. Retinal thickness on the first post-operative day showed significant increase in two studies 9,10 and mild statistically insignificant decrease in one study.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…OCT also showed that after 180 days post-op, three eyes without DR developed mild NPDR without ME, and two eyes with moderate NPDR without ME developed moderate DR with ME. Cataract surgery has the potential to induce inflammatory and mechanical changes in vitreoretinal structures, thus causing macular thickening with changes to VA (8) , probably due to damage to the blood-retinal barrier (9,10) . Jun et al (11) evaluated 637 OCT exams (Stratus) in patients with ma cular diseases and CFT scores less than 252 µm.…”
Section: Discussionmentioning
confidence: 99%